THE ROLE OF FAMILY IN JOHN STEINBECK’S THE GRAPES OF WRATH - Titis Setyabudi (Universitas Muhammadiyah Surakarta, 2011)
This is an analysis of John Steinbeck’s novel The Grapes of Wrath conducted using structuralism approach. The result shows that the meaning of family in The Grapes of Wrath has two supporting dimensions. First, a family is nuclear family consisting of a father, mother and children. They live as a household and in one house. Sometimes, they consider extended family particularly grandfather, grandmother, uncles, and others. Second, a family is a group of people with same backgrounds and problems. In The Grapes of Wrath, the meaning of family dramatically is gained from their family bond and togetherness at Route 66.Key words: Family, Structuralism, The Grapes of Wrath, John Steinbeck